Entry, competence-destroying innovations, volatility and growth: Lessons from different industries - Mariana Mazzucato (The Open University, Economics Department, 2004)
Periods of Schumpetarian creative destruction are well captured by indicators of turbulence that highlight changes in inter-firm variety, such as the market share instability index and relative growth rates. Entry/exit rates do not always serve this purpose. The point is illustrated through the case of the personal computer industry which experienced high entry rates (and high absolute firm growth rates) simultaneously with incremental innovation and relative stability in the market shares of the incumbent firms. The period of radical innovation that occurred in the PC industry after the period of high entry/exit was characterized by large changes in market shares and relative growth rates. Besides market share instability, different indices of stock price volatility (excess volatility and idiosyncratic risk) also prove to successfully capture periods of radical innovation. After developing these points using detailed data for the auto and PC industries, the correlation between innovation and volatility is studied in 34 industries with different levels of innovativeness. The results provide new insights into the dynamics of economic growth driven by General Purpose Technologies (GPTs).
Keywords: 330; radical innovation; market structure; volatility; growth